Effect of cold argon plasma on eggs of the blow fly, Lucilia cuprina (Diptera: Calliphoridae) - Kwankamol Limsopatham (2018)
© 2017 Elsevier B.V. Non-thermal plasma has been used in many medical applications, including treatment of living cells, blood coagulation, wound healing, and sterilization. The process uses an environmentally friendly gas (e.g., argon, helium, oxygen, nitrogen, or hydrogen) to destroy bacteria cells with no serious adverse effect on humans or animals. However, information on the effect of argon plasma on blow fly eggs is lacking. In this study, we explored the ability of cold argon plasma to destroy the eggs of the Australian sheep blow fly, Lucilia cuprina (Wiedemann, 1830); its larvae are a myiasis-producing agent in both human and animals. We tested the effect of cold argon plasma exposure for 1, 2, 3 and 5 min on L. cuprina eggs. Since the temperature of cold Ar plasma is around 30 °C, to clarify the effect of temperature on the fly eggs, hot air from an electric dryer was tested for comparison. Cold argon plasma exposure in eggs significantly reduced the survival rates of second instar larvae at all exposures tested; the effects were time dependent, with a stronger effect at longer exposure (32% survival rate after a 1-min treatment; 20%, 2 min; 20%, 3 min; and 6%, 5 min), compared to the control (86%). No significant differences were observed in larval survival rates from eggs treated with hot air (80-84%, after 1- to 5-min treatments) versus the control (86%). These results were supported by observing the treated eggshells under a scanning electron microscope (SEM), we found noticeable aberrations only in the plasma treated groups. The emission spectrum of the argon gas discharge revealed emission lines of hydroxyl radicals at 309.1 nm; these may cause the deterioration of the treated L. cuprina eggs. Our results have shown the possibility of using cold argon plasma in medical applications, in particular treating myiasis wounds.